Pengembangan skenario pembelajaran fisika berbasis kompetensi - Mundilarto Mundilarto (LPMPP Universitas Negeri Yogyakarta, 2006)
By using the power resources available at school, teachir are hoped to have knowledge and skills in developing the teaching and learning of physics in order to make learners acheve competency through many kinds of learning activities. A teaching and learning scenario is needed as an operational teachers guide in developing both the learning process in class and outdoor learning activities. The problem is that most teachers of physics still have insufficient skills to develop a competency-based teaching and learning scenario of physic. This artikel is to help them with a reding material that may increase thir comprehension of and knowledge in designing and developing such a scenario. They will benefit by having better skills in and knhwledge of desingning and developing that kind of scenario.The teaching and learning of physics must be directed to developing not only student competency in the cognitive domain but also thir competencies in the psychomotor and affective domain.